Patients' Knowledge and Attitude toward the Disposal of Medications. (10th October 2017) - AlAzmi, Aeshah; AlHamdan, Hani; Abualezz, Rayf; Bahadig, Faiz; Abonofal, Noha; Osman, Mohamed
Abstract : Background . Safe disposal of medications is of high concern as malpractice may lead to harmful consequences such as undesirable effects, prescription drug abuse, overstocking, self-medication, accidental overdose, and even death. There is a lack of uniform and nationwide guidance on how patients should safely dispose their leftover medications. This study aims to assess patients' knowledge and attitude regarding the disposal of medications. Method . This research is a cross-sectional study. A self-administered questionnaire was used to collect data from various outpatient pharmaceutical services in King Abdulaziz Medical City (KAMC), Jeddah. Results . The study revealed that 73% of the respondents throw the medications in the trash, 14% return the medications to a pharmacy, 5% never dispose them, and 3% donate the medications to a friend or charity centers. More than 80% of the respondents never received any information or advice from healthcare providers about safe and proper disposal of medications. Conclusion . Our findings suggest that there is an immediate requirement for the establishment of collaborative and uniform guidelines for the safe disposal of leftover medications. A policy for drug donation needs to be included in routine patient education as well as educational and collective programs for the public.